Large-area, green solvent spray deposited nickel oxide films for scalable fabrication of triple-cation perovskite solar cells. Issue 6 (27th January 2020) - Kumar, Neetesh; Lee, Hock Beng; Hwang, Sunbin; Kang, Jae-Wook
Abstract : A large-scale (64 cm 2 ), spray-coated nickel oxide (NiO) film as a hole-transport layer has successfully yielded >17% efficiency in planar triple-cation perovskite solar cells (PSCs). Abstract : Fabrication of high-quality, low-cost and large-scale solution processable inorganic hole-transport layers (HTLs) for planar p–i–n perovskite solar cells (PSCs) is still a challenge that must be overcome to produce stable devices. Herein, we demonstrate the development of large-scale (>60 cm 2 ), highly uniform and dopant-free NiO films via spray pyrolysis, and we show their subsequent application as a HTL in triple-cation PSCs. The spray deposited NiO films are highly crystalline in nature with a (111) oriented nanostructured morphology. We show outstanding optoelectronic properties ( E g ≈ 3.78 eV, work function ≈ 4.86 eV) that led to improved optical absorption and better energy band alignment with the perovskite layer. Compared to the state-of-the-art PEDOT:PSS based PSCs, these spray-deposited NiO-based devices exhibited an excellent power conversion efficiency (PCE) of ∼17.3%, which is the highest reported value for dopant-free NiO-based PSCs prepared via the spray-deposition technique. More importantly, the NiO based PSCs also showed extremely high reproducibility and scalable device performance, achieving a PCE of 12.3% at an aperture area of ∼1.04 cm 2 . Moreover, unencapsulated PSCs employing spray-deposited NiO exhibited outstanding stability, maintaining ∼87% PCE after 4500 h of aging in a N2 atmosphere, and encapsulated devices exhibited much better stability retaining >82% of the initial PCE after 200 h in a harsh environment (85 °C, 85% relative humidity).